The Worst We Can Find: MST3K, RiffTrax, and the History of Heckling at the Movies - Sherman, Dale (Rowman & Littlefield Publishers, 2023)
Had you tuned in to the small television station KTMA on Thanksgiving Day, 1988, you would have been one of the few witnesses to pop culture history being made. On that day, viewers in and around St. Paul, Minnesota, were treated to a genuine oddity, in which a man and his robots, trapped within a defiantly DIY sci-fi set, cracked jokes while watching a terrible movie. It was a cockeyed twist on the local TV programs of the past, in which a host would introduce old, cheaply licensed films. And though its origins may have been inauspicious, Mystery Science Theater 3000 captured the spirit of what had been a beloved pastime for generations of wags, wiseacres, and smartalecks, and would soon go on to inspire countless more. The Worst We Can Find is a comprehensive history of and guide to MST3K and its various offshoots—including Rifftrax, Cinematic Titanic, and The Mads Are Back—whose lean crew of writers, performers, and puppeteers have now been making fun of movies for over thirty years. It investigates how “riffing” of films evolved, recounts the history of these programs, and considers how a practice guaranteed to annoy real-life fellow moviegoers grew into such a beloved, long-lasting franchise. As author Dale Sherman explains, creative heckling has been around forever—but MST3K and its progeny managed to redirect that art into a style that was both affectionate and cutting, winning the devotion of countless fans and aspiring riffers.